Sum throughput maximization for downlink MIMO-OFDMA based cognitive radio networks in spectrum overlay model - Mohammadi, Mahla; Andargoli, Seyed Mehdi Hosseini (2016 8th International Symposium on Telecommunications (IST), 2016)
In this paper, the resource allocation for MIMO-OFDMA based cognitive radio (CR) network subject to primary user's (PU)'s constraints is considered. The optimal resource allocation strategy is proposed subject to the total power constraint in the cognitive base station (CBS) and the interference power constraint on the primary users. To this aim, two sub-problems are presented and solved theoretically based on convex optimization framework that can be used in the main body of the proposed algorithm. So, in order to find the optimum solution, our algorithm consists of three sections which are included these sub-problems. Simulation results show that the proposed algorithm achieves better performance in comparison with a benchmark algorithm and converges to sub-problem solutions in high and low regime of interference thresholds.